2000
DOI: 10.1086/315217
|View full text |Cite
|
Sign up to set email alerts
|

Extended Virulence Genotypes ofEscherichia coliStrains from Patients with Urosepsis in Relation to Phylogeny and Host Compromise

Abstract: Among 75 urosepsis isolates of Escherichia coli, 29 virulence factor (VF) genes were detected by use of a novel polymerase chain reaction (PCR) assay. Compared with probe hybridization, the PCR assay's specificity was 100% and sensitivity 97.1%. fyuA (yersiniabactin: overall prevalence, 93%), traT (serum resistance, 68%), and a pathogenicity-associated island marker (71%) occurred in most strains from both compromised and noncompromised hosts. Present in <20% of strains each were sfaS, focG (F1C fimbriae), afa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
971
11
20

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,129 publications
(1,062 citation statements)
references
References 85 publications
60
971
11
20
Order By: Relevance
“…PCR method is highly specific, informative and a powerful genotypic assay, used for detection of adhesin-encoding operons and other virulence factors that can also contribute to virulence in UTI. In this study, we confirmed the prevalence of fimH among UPEC strains 10,21,23 . FimH occurred in 158 strains.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…PCR method is highly specific, informative and a powerful genotypic assay, used for detection of adhesin-encoding operons and other virulence factors that can also contribute to virulence in UTI. In this study, we confirmed the prevalence of fimH among UPEC strains 10,21,23 . FimH occurred in 158 strains.…”
Section: Discussionsupporting
confidence: 83%
“…Bacterial DNA to be amplified was released from whole organisms by boiling, and a multiplex PCR assay was carried out in a total volume of 25 µL, containing 2 µL of template DNA, each of the primers at 60 ng, the four deoxynucleotide triphosphates (each at 200 µM), PCR buffer 1X and 1.5 U of Taq DNA polymerase 3,10 . For Multiplex PCR, amplifications consisted of 25 cycles of 94 ºC for one min, specific annealing temperature for each primer for one min (Table1), 68 ºC for three min, and a final extension at 72 ºC for seven min in a Thermal Cycler (Gene Amp PCR System 9700/Perkin Elmer Corporation, Norwal CT/USA).…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…ExPEC are able to subvert the host immune response within the urinary tract through the production of conjugal transfer surface exclusion protein (TraT), an outer membrane protein associated with serum resistance (39) aer and hly were more prevalent amongst patients with pyelonephritis compared with those suffering from cystitis. While these associations must be interpreted with caution, they do provide evidence to support the theory that VF profiles are likely to be associated with the propensity of ExPEC to cause site-specific disease within the urinary tract.…”
Section: Urinary Tract Infection-associated Vfsmentioning
confidence: 99%
“…host factors, and their associations with susceptibility to and severity of infection. In relation to UTI, for example, host factors associated with an increased risk of infection include being female (shorter urethral length), anatomical abnormalities of the urinary tract, a pre-existing diagnosis of diabetes mellitus, and the presence of an indwelling urinary catheter (7,39,68).…”
Section: Expec As An Intestinal Colonistmentioning
confidence: 99%
“…The first five panels have been described elsewhere [22] Additionally, another multiplex amplification procedure was used to detect sitA, feoB, and irp2. Amplification of these genes was performed in a 25 µL reaction that included 2 µL of template DNA, 18.9 µL of double distilled water (ddH 2 O), 1.5 µL of 10× PCR Buffer, 0.75 µL of 50 mM MgCl 2 , 0.25 µL of DNA Taq Polymerase (Invitrogen, Carlsbad, CA, USA) 1.0 µL of a dNTP mixture with a concentration of 2.5 mM of each dNTP (USB, Cleveland, Ohio, USA), and 0.1 µL of 0.1 mM upper and lower primers.…”
Section: Virulence Genotypingmentioning
confidence: 99%